Original Short Stories $1 (BVolume 09s - Maupassant, Guy de, 1850-1893; Henderson, A. E.; McMaster, Albert Cohn; Quesada, Louise Charlotte Garstin (Salt Lake City, UT : Project Gutenberg, 2004)
"Original Short Stories $1 (BVolume 09" by Guy de Maupassant is a collection of short stories written during the late 19th century. The volume showcases a diverse array of narratives that explore themes of human experience, relationships, and social commentary, all characterized by Maupassant's keen eye for detail and mastery of storytelling. The collection begins with the lively character of Toine, a jovial innkeeper whose robust personality and interactions with his wife and patrons set the stage for humorous yet poignant reflections on life. At the start of the volume, the tale "Toine" introduces readers to Antoine Macheble, affectionately known as Toine or (3z(BBurnt-Brandy,(3y (Ba beloved innkeeper whose size and character are notable in the small hamlet of Tournevent in Normandy. Described as a giant of a man with a hearty appetite for food and drink, Toine's life takes a turn when illness confines him to his bed, leading to comedic exchanges with his wife and adventures with friends who continue to seek his company. His humorous attempts to hatch chickens using warmth from his body add whimsical elements to the story, showcasing Maupassant's ability to blend humor with deeper insights into human resilience and social bonds. (This is an automatically generated summary.)s
Toine -- Madame Husson's rosier -- The adopted son -- A coward -- Old Mongilet -- Moonlight -- The first snowfall -- Sundays of a bourgeois -- A recollection -- Our letters -- The love of long ago -- Friend Joseph -- The effeminates -- Old amable.
Release date is 2004-10-03
Produced by David Widger
Keywords: Short stories, French -- Translations into English